“If you prick us, do we not bleed?” Antisemitism and psychosocial health among Jews in Germany - Shani, Maor; Goldberg, Dana; van Zalk, Maarten H. W. (Frontiers in Psychology, 2025)
IntroductionAmid escalating global antisemitism, particularly following the Hamas attack on Israel on October 7, 2023, this study addresses critical gaps in understanding the psychosocial impact of antisemitism on Jewish communities worldwide.MethodsFocusing on the Jewish community in Germany, we conducted a cross-sectional survey of 420 Jewish individuals (mean age = 40.71 years, SD = 15.90; 57% female). Participants completed measures assessing four distinct forms of perceived and experienced antisemitism: everyday discrimination, microaggressions (subtle antisemitism and collective experiences such as encountering antisemitic comments on social media), vigilance against antisemitism, and perceived prevalence of antisemitism. Psychosocial outcomes—including depression, anxiety, subjective well-being, and social participation—were also measured. Data were analyzed using correlation analyses and multiple linear regressions, and Latent Profile Analysis (LPA) identified distinct groups based on shared perceptions and experiences of antisemitism and levels of Jewish identification.ResultsResults indicate that experiences of antisemitism, particularly everyday discriminatory acts, were significantly associated with poorer mental health outcomes and reduced social participation. The LPA revealed three distinct groups, with the high-identity, high-antisemitism group (53% of the sample) reporting significantly higher anxiety levels than those with average identification and more rare experience with antisemitism.DiscussionThese findings underscore the pervasive nature of antisemitism and its detrimental effects on the well-being of Jewish individuals. The study highlights the need for targeted interventions to promote resilience within Jewish communities and calls for broader societal efforts to combat antisemitism.